Design and Characterization of Pentoxifyllinepharmacosomes by Solvent Evaporation Method - V. Viswanath (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Aim The objective of the present investigation is to formulate the Pentoxifyllinepharmacosomes using 32 factorial design technique. Methods Pentoxifylline is drug of choice for treatment of patients with intermittent claudication on the basis of chronic occlusive arterial disease of the limbs and is a BCS class II drug. Pentoxifyllinepharmacosomes were prepared by solvent evaporation method using variable concentrations of Lecithin. The formulation design is developed by altering the concentrations of Pentoxifylline and Lecithin in a fixed ratio and considered as independent variables assigned X1 and X2 respectively. Whereas, the time required to release 10% (t10%), 50% (t50%), 75% (t75%), and 90% (t90%) are considered as the dependent variables. The design developed total 9 formulations which were formulated and evaluated as per the pharmacopoeial tests. Results The results reveal that the developed formulations are in the pharmacopoeial limits. Further, the formulations are subjected to in-vitro drug release studies through kinetic modeling which ultimately lead to the development of slope, intercept and regression coefficient. The resultant is implied for the generation of various polynomial equations for t10%, t50%, t75%, and t90% drug release which confirms the optimized formulation as F1. Conclusion Based on the results it can be concluded that the best optimized formulation is F1 and follows first order kinetics. Further, Higuchi kinetics reveals that the formulation follows non-Fickian diffusion anomalous transport (n= 0.723)